Effects of the family customised online FOCUS programme on patients with heart failure and their informal caregivers: a multicentre, single-blind, randomised clinical trialResearch in context - Weiling Yang; Li Sun; Lili Hao; Xiaonan Zhang; Qingyun Lv; Xueying Xu; Yaqi Wang; Yanting Li; Lihui Zhou; Yue Zhao; Xiaoying Zang; Yaogang Wang (EClinicalMedicine, 2024)
Summary: Background: Living with heart failure can severely affect the physical and mental health of patients with heart failure and their caregivers. Available dyadic self-care interventions for heart failure are scarce, especially in China. We aimed to develop and test the family FOCUS programme. Methods: This single-blind, randomised, controlled study was conducted at four hospitals in Tianjin, China. Patients with heart failure (aged at least 18 years) and their caregiver (dyads) were randomly assigned to either the intervention (n = 71) or control (n = 71) group in a 1:1 ratio. The primary outcomes of this study were patient self-care, with three specific dimensions (self-care maintenance, symptom perception, and self-care management), and caregiver contribution to self-care, mirroring these three dimensions. The outcomes were assessed at baseline (T0) and 4 (T1), 12 (T2), and 24 (T3) weeks post-discharge, respectively. This work is registered on ChiCTR, ChiCTR2100053168. Findings: Between May 20, 2022, and September 30, 2022, 142 dyads with heart failure were enrolled. The intervention group exhibited dropout rates of 6%, 8.5%, and 18.3% at 4, 12, and 24 weeks after discharge, while the control group showed 9.9%, 12.3%, and 25.4%. Compared with the control group, patients in the intervention group reported improved self-care maintenance (β: 8.5, 95% CI: 0.7, 16.4) and management (β: 7.2, 95% CI: 0.1, 14.3) at T1, as well as improved symptom perception at both T1 (β: 9.7, 95% CI: 1.5, 17.9) and T2 (β: 9.6, 95% CI: 0.6, 18.6). Furthermore, caregiver contributions to self-care maintenance, self-care management, and symptom perception (excluding T3) exhibited significant improvements at all timepoints. Interpretation: Although the significant improvements in patients' self-care were not long-lasting, this study suggested that the family FOCUS programme consistently enhanced caregivers' contributions to self-care. Future work could explore the effect of the family FOCUS programme on families with multiple chronic conditions. Funding: The National Natural Science Foundation of China.